The role of enzymes of the glyoxalase system in relation to complications in type II diabetes mellitus - Patke, Vinay Govind; Saroj, Sarvesh R. (International Journal of Research in Medical Sciences, 2017)
Background: Metabolism of methylglyoxal by the glyoxalase system may be linked to the development of diabetic complications. It was considered worthwhile to find out whether changes observed in the levels of glyoxalase I, glyoxalase II, aldose reductase & D-lactate are prognostic indicators for the development of complications of diabetes or merely reflect the result of changes associated with complications. Methods: The glyoxalase system was characterized in erythrocytes of blood samples from patients with type II diabetes mellitus (n=177), and normal healthy control subjects (n=40). Diabetics were divided into 3 main groups based on presence or absence of complications. Results: The concentrations of RBC glyoxalase I, glyoxalase II, aldose reductase, and D-lactate were significantly increased in all groups of diabetic patients, (P <0.001) relative to controls. Comparison between groups showed maximum rise of enzymes in group I and group III (P <0.001); and maximum rise of D-lactate in group III (P <0.001). Within the groups of patients with complications, enzyme levels were markedly increased in patients with IHD/PVD (ischaemic heart disease/peripheral vascular disease) and decreased in patients with nephropathy. Conclusion: Results of this study suggests a positive relationship between increased activity of erythrocyte enzymes of glyoxalase system and poor or moderate glycemic control. The increased enzyme levels in patients without complications indicate their role as prognostic markers for development of complications. Molecular mechanisms for development of Nephropathy appear to be different from those of Neuropathy and Retinopathy.